(untitled) (International Seven Journal of Health Research, 2025)
The chromosomopathies that generate congenital heart diseases represent one of the main challenges for neonatal public health in Brazil, affecting about 30 thousand newborns annually. Data from DATASUS and the Information System on Live Births (SINASC) indicate significant underreporting, with only 5.3% of the estimated cases officially registered. The global prevalence of 9 cases per 1,000 live births is used as a parameter to estimate the national figures, which point to a significant burden of the disease. About 40% of affected newborns require surgical intervention in the first year of life, highlighting the importance of early diagnosis and specialized follow-up. This article discusses the challenges related to data collection, the formulation of public policies, and strategies to improve the care of patients with chromosomal diseases in the Northwest of São Paulo.